USE OF COLLABORATIVE LEARNING STRATEGIES IN FORMING INTERPERSONAL INTELLIGENCE WHERE IS NURUL AKBAR PONGKA KAB. BONE - Hajar Humaera Cane; Samsinar Samsinar; Aminullah Aminullah (Penelitian dan Pengembangan Ilmu, 2025)
This study examines the application of collaborative learning strategies in developing students' interpersonal intelligence at MA Nurul Akbar Pongka, Bone Regency. Using a qualitative field research design and an educational approach, data were collected through interviews, observations, and documentation. The collaborative strategy was implemented through three stages: planning, implementation, and evaluation. The planning stage involved designing group work that focused on building social character; implementation encouraged positive interactions and joint decision-making; and evaluation included assessing group outcomes, individual participation, and social attitudes. The results showed that collaborative learning improved students' interpersonal intelligence, including self-confidence in communication, listening skills, and conflict resolution. This strategy also fostered cooperation, tolerance, and mutual support among students.